(untitled) (Damascus University Journal for the economic and Political sciences, 2026)
The study aimed to determine the extent to which strategic leadership in its dimensions (administrative, transformational, political, and ethical) contributes to reducing organizational aging at MTN Company. The study used the descriptive approach with an analytical approach. The questionnaire was used as a tool for collecting data and /80/completed questionnaires distributed among employees of MTN Company’s Human Resources Department were analyzed. The study found several results, including: The evaluation of strategic leadership in its dimensions (administrative, transformational, political, ethical) was at a high level according to the opinions of employees at MTN Company, and the level of evaluation of Organizational aging is at a low level, according to the opinions of MTN employees, and there is a significant impact of strategic leadership in reducing organizational aging in MTN. The researcher recommended that MTN must provide a positive organizational climate that supports constructive thinking, provide the appropriate leadership style for managers which meets the ambitions of the employees and achieves the company’s strategic goals, keep pace with the development of services and offers that attract customers, and provide advanced modern technologies to keep up with technological developments by building modern technological systems that will lead them to pioneering.